Reliability of benefit value transfers from contingent valuation data with forest-specific attributes - Riccardo Scarpa; George W. Hutchinson; Sue M. Chilton (Fondazione Eni Enrico Mattei (FEEM), 2000)
We investigate the reliability of transferring benefit estimates of forest recreation obtained from discrete choice CV data and conditional on forest-specific attributes. The transfer reliability is checked against the forest-specific estimates of mean and median willingness to pay. We report and discuss the outcomes of formal tests of the null hypothesis of no difference for 26 recreational forests in Ireland, when the value transfer is based on single and double-bounded data collected at the remaining 25 forests. Contrary to the unconditional value transfers of Downing and Ozuna [6] we find that value transfers conditional on site-specific recreational attributes are mostly transferable.
Keywords: C81; Q23; Q26; 330; Benefit transfer; estimate reliability; forest recreation; non-market valuation; discrete-choice contingent valuation; Willingness to pay; Tourismusregion; Wald; Schätzung; Irland; Nordirland